1998
DOI: 10.2307/3237123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil texture and precipitation on above‐ground net primary productivity and vegetation structure across the Central Grassland region of the United States

Abstract: Abstract. A potentially important organizing principle in arid and semi‐arid systems is the inverse‐texture hypothesis which predicts that plant communities on coarse‐textured soils should have higher above‐ground net primary productivity (ANPP) than communities on fine‐textured soils; the reverse is predicted to occur in humid regions. Our objectives were: (1) to test predictions from the inverse‐texture hypothesis across a regional precipitation gradient, and (2) to evaluate changes in community composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 37 publications
(52 reference statements)
5
73
1
3
Order By: Relevance
“…Among the most noticeable hypotheses is the inverse-texture hypothesis (ITH) [Noy-Meir, 1973], which states that production is higher on coarse-textured soils than that on fine-textured soils in dry regions because the water availability will be high in coarse soil in dry regions. The hypothesis has been supported by many studies [e.g., Sala et al, 1988;Lane et al, 1998;Epstein et al, 1997]. According to observations from central grassland regions in the United States, sandy soils are more productive than loamy soils when annual precipitation is less than 370 mm [Sala et al, 1988].…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Among the most noticeable hypotheses is the inverse-texture hypothesis (ITH) [Noy-Meir, 1973], which states that production is higher on coarse-textured soils than that on fine-textured soils in dry regions because the water availability will be high in coarse soil in dry regions. The hypothesis has been supported by many studies [e.g., Sala et al, 1988;Lane et al, 1998;Epstein et al, 1997]. According to observations from central grassland regions in the United States, sandy soils are more productive than loamy soils when annual precipitation is less than 370 mm [Sala et al, 1988].…”
Section: Introductionmentioning
confidence: 50%
“…In central grassland region of U.S.A., the soil texture ranged from sand and sandy loam to silt loam and silt clay loam. Soil water holding capacity among those soil types ranged from 0.062 to 0.33 g water g À1 soil [Lane et al, 1998]. We assigned five soil texture types to cover the whole range in nature.…”
Section: G03003mentioning
confidence: 99%
“…In the Haut-Saint-Laurent, in Quebec, Meilleur et al (1992) observed no effect of soil texture on vegetation. In a steppe in the USA, more shrub species were found in intermediate soil textures, whereas more herbaceous species were encountered when soil texture was finer (Dodd and Lauenroth 1997;Lane et al 1998). However, even in these studies, soil texture did not have a significant effect on the aboveground net primary production (Lane et al 1998).…”
Section: Influence Of Dominant Vegetation Height and Density On The Amentioning
confidence: 97%
“…In coarse soils forbs and shrubs made up a larger proportion of total productivity as compared to fine-textured sites. Thus across a regional precipitation gradient, soil texture may play a larger role in determining community composition than in determining total ANPP (Lane et al, 1998) …”
Section: Biomass Productivity 41 Factors That Influence Savanna Prodmentioning
confidence: 99%